A peridynamic mechano-chemical damage model for stress-assisted corrosion. (10th November 2019) - Jafarzadeh, Siavash; Chen, Ziguang; Li, Shumin; Bobaru, Florin
Abstract: We introduce a mechano-chemical coupled peridynamic model for stress-assisted corrosion. In the model, the activation-controlled anodic dissolution is a function of nonlocal dilatation of material near the corrosion front. We use a new experimental design to measure anodic dissolution rate for copper under activation-controlled and applied tensile stress. The experimental results are used to calibrate and then validate the new model. A case for stress-assisted corrosion in a complex geometry with non-uniform stress distribution is included to demonstrate the model's capabilities. Graphical abstract: Image 1 Highlights: A new mechano-chemical coupled peridynamic model for stress-assisted corrosion. Anodic dissolution is a function of stress/strain (dilatation) in metal near corrosion front. Experimental results show effect of tensile stress on activation-controlled anodic dissolution. Validation against experimental results for stress assisted corrosion of Copper in NaCl solution. Demonstration of corrosion damage evolution in a loaded tapered plate with corroding holes.